Prawo autorskie jako element kształcenia artystycznego oraz podstawa działalności kulturalnej szkół = Copyright law as a part of artistic curriculum and basis for schools` cultural activities - Laskowska, Ewa; Mania, Grzegorz (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The paper presents copyright institutions that are essential for schools, particularly for conducting cultural activities. Firstly, the Authors analyse fair use exceptions that allows to exploit creativity without permission and royalties. Secondly, the article discusses the matters of work-of-hire at schools and presents basic terms of copyright law. Finally, the Authors show how to educate about copyright and incorporate it in curriculums.
Keywords: prawo autorskie; dzieło; dozwolony użytek; ochrona; copyright law; fair use; work-of-hire; work; protection